Paediatric ED BiPAP continuous quality improvement programme with patient analysis: 2005–2013. Issue 1 (16th January 2017) - Abramo, Thomas; Williams, Abby; Mushtaq, Samaiya; Meredith, Mark; Sepaule, Rawle; Crossman, Kristen; Burney Jones, Cheryl; Godbold, Suzanne; Hu, Zhuopei; Nick, Todd
Abstract : Objective: In paediatric moderate-to-severe asthmatics, there is significant bronchospasm, airway obstruction, air trapping causing severe hyperinflation with more positive intraplural pressure preventing passive air movement. These effects cause an increased respiratory rate (RR), less airflow and shortened inspiratory breath time. In certain asthmatics, aerosols are ineffective due to their inadequate ventilation. Bilevel positive airway pressure (BiPAP) in acute paediatric asthmatics can be an effective treatment. BiPAP works by unloading fatigued inspiratory muscles, a direct bronchodilation effect, offsetting intrinsic PEEP and recruiting collapsed alveoli that reduces the patient's work of breathing and achieves their total lung capacity quicker. Unfortunately, paediatric emergency department (PED) BiPAP is underused and quality analysis is non-existent. A PED BiPAP Continuous Quality Improvement Program (CQIP) from 2005 to 2013 was evaluated using descriptive analytics for the primary outcomes of usage, safety, BiPAP settings, therapeutics and patient disposition. Interventions: PED BiPAP CQIP descriptive analytics. Setting: Academic PED. Participants: 1157 patients. Interventions: A PED BiPAP CQIP from 2005 to 2013 for the usage, safety, BiPAP settings, therapeutic response parameters and patient disposition was evaluated using descriptive analytics. Primary and secondary outcomes: Safety, usage, compliance, therapeutic response parameters, BiPAP settings and patient disposition. Results: 1157 patients had excellent compliance without complications. Only 6 (0.5%) BiPAP patients were intubated. BiPAP median settings: IPAP 18 (16, 20) cm H2 O range 12–28; EPAP 8 cmH2 O (8, 8) range 6–10; inspiratory-to-expiratory time (I:E) ratio 1.75 (1.5, 1.75). Pediatric Asthma Severity score and RR decreased (p<0.001) while tidal volume increased (p<0.001). Patient disposition: 325 paediatric intensive care units (PICU), 832 wards, with 52 of these PED ward patients were discharged home with only 2 hours of PED BiPAP with no returning to the PED within 72 hours. Conclusions: BiPAP is a safe and effective therapeutic option for paediatric patients with asthma presenting to a PED or emergency department. This BiPAP CQIP showed significant patient compliance, no complications, improved therapeutics times, very low intubations and decreased PICU admissions. CQIP analysis demonstrated that using a higher IPAP, low EPAP with longer I:E optimises the patient's BiPAP settings and showed a significant improvement in PAS, RR and tidal volume. BiPAP should be considered as an early treatment in the PED severe or non-responsive moderate asthmatics.